Neighbours of a family with a disabled person - Górnicka, Beata (Kultura-Społeczeństwo-Edukacja, 2021)
Nowadays, social changes include the perception not only of disability itself, but also of a family with a disabled member. These changes concern the organisation of support for the family, which functions in the entire social ecosystem, including the closest social groups, e.g., the neighbourhood. Although this neighbourhood, which is also subject to changes, can become an invaluable source of support, unfortunately, it may also become an environment that contributes to the social exclusion of a family. In this paper, the author presents selected aspects of the co-existence of people with disabilities and their families with their neighbours. The paper used research on opinions about being the neighbour of a family with a disabled person, which included declarations of help or support really offered. The author asserts that a family with a disabled person can experience both positive and negative attitudes and behaviours from neighbours.